Current-induced three-dimensional domain wall propagation in cylindrical NiFe nanowires - Wong, D. W. (2017)
We report on the magnetization configurations in single NiFe cylindrical nanowires grown by template-assisted electrodeposition. Angular anisotropic magnetoresistance measurements reveal that a three-dimensional helical domain wall is formed naturally upon relaxation from a saturated state. Micromagnetic simulations support the helical domain wall properties and its reversal process, which involves a splitting of the clockwise and anticlockwise vortices. When a pulsed current is applied to the nanowire, the helical domain wall propagation is observed with a minimum current density needed to overcome its intrinsic pinning.